2017
DOI: 10.1111/pbi.12760
|View full text |Cite
|
Sign up to set email alerts
|

Engineering heat tolerance in potato by temperature‐dependent expression of a specific allele of HEAT‐SHOCK COGNATE 70

Abstract: SummaryFor many commercial potato cultivars, tuber yield is optimal at average daytime temperatures in the range of 14–22 °C. Further rises in ambient temperature can reduce or completely inhibit potato tuber production, with damaging consequences for both producer and consumer. The aim of this study was to use a genetic screen based on a model tuberization assay to identify quantitative trait loci (QTL) associated with enhanced tuber yield. A candidate gene encoding HSc70 was identified within one of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…To confirm these observations and provide quantitative evaluation of the thermotolerance, we determined how the cell membrane integrity changes in these cultivars in response to temperatures by measuring leakage of electrolytes ( Ahn et al, 2004 ; Savić et al, 2012 ; Trapero-Mozos et al, 2018 ). In this work, potato leaf disks were subjected to high (47°C) and normal (22°C; control) temperatures for 5 h, and electrolyte leakage was calculated by measuring the percentage of difference in conductivity between the samples at 47 and 22°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm these observations and provide quantitative evaluation of the thermotolerance, we determined how the cell membrane integrity changes in these cultivars in response to temperatures by measuring leakage of electrolytes ( Ahn et al, 2004 ; Savić et al, 2012 ; Trapero-Mozos et al, 2018 ). In this work, potato leaf disks were subjected to high (47°C) and normal (22°C; control) temperatures for 5 h, and electrolyte leakage was calculated by measuring the percentage of difference in conductivity between the samples at 47 and 22°C.…”
Section: Resultsmentioning
confidence: 99%
“…To assess thermotolerance by measuring cell membrane injury, an electrolyte leakage assay was carried out, essentially as described in Trapero-Mozos et al (2018) . Four 10-mm leaf disks each from a different leaf per plant were placed in test tubes containing 5 mL of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were stored at −80°C prior to lyophilization, extraction, and analysis. Samples were extracted as polar and non-polar phases, derivatized, and analyzed by gas chromatography mass spectrometry (GC-MS) as previously described (Dobson et al, 2008;Trapero-Mozos et al, 2018b). Metabolite profiles were acquired using a GC-MS (DSQII Thermo-Finnigan, UK) system carried on a DB5-MSTM column (15 m × 0.25 mm × 0.25 μm; J&W, Folsom, CA, USA) as described by Foito et al (2013).…”
Section: Metabolite Profiling By Gas Chromatography Mass Spectrometrymentioning
confidence: 99%
“…Very similar patterns of gene expression were observed using both techniques (Online Resource S12). The selected HSPs, used as test genes, were those previously implicated in acclimation processes (HSP17.6 and HSP101; McLoughlin et al 2016 ) and a potato HSC70 gene recently demonstrated to protect against elevated temperature in potato (Trapero-Mozos et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Potato elongation factor1-alpha (EF1α) primers were used as a control. Quantitative PCR was performed as previously described (Trapero-Mozos et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%